Pengaruh Pencampuran Media Tanam Serta Beda Ukuran Benih Terhadap Pertumbuhan Biji Kamboja Jepang (Adenium crimsonstar) - Kukuh Dwi Styawan; Rustam Baraq Noor; Abdul Rofik (Agrifarm : Jurnal Ilmu Pertanian, 2012)
As well as the growing influence of media mixing different grain size of the seed to growth frangipani Japan (Adenium crimsonstar). This study aims to determine the effect of mixing different media as well as the planting of seed size on seed growth frangipani Japan (Adenium crimsonstar). The study was conducted in April through July 2010, in the district of Ulu Loa Janan, Kutai regency. This study uses a completely randomized design (CRD) with 4 x 3 factorial analysis consisted of four replications. The first factor is the growing media 4 levels: m0: sand medium (control), m1: sand + fine brick (3: 1), m2: sand, ground roasted (3: 1), m3: finely + sand + bricks ground fuel (2 : 1: 1). The second factor is the size of the seed 3 levels: b1: weight 0,02gram / 0.9 to 1.0 cm long seed / seed, b2: 0,01gram / 0.5-0.7 cm long beans / seeds, b3: weight of 0,008 gram / seed length from 0.3 to 0.4 cm / seed. The results showed that treatment Growing Media significant effect on all parameters of the study. Treatment m2 (sand + soil fuel) showed the highest plant height is 5.44 cm, while the treatments m1 (fine brick sand +) showed the smallest plant height is 3.07 cm, the results showed that the different treatment of seed size did not significantly affect all parameter studies. Media interaction and different planting seed size showed no significant difference in all parameters of the study.